LEARN EARTH ROTATION AND REVOLUTION: PENGEMBANGAN MEDIA GEOROTATION UNTUK PEMBELAJARAN DIGITAL GEOGRAFI - Annisa Khusnul Khotimah; Djoko Soelistijo; Alfyananda Kurnia Putra; Yohana Ayu Kristanti (Jurnal Praksis dan Dedikasi Sosial (JPDS), 2023)
LEARN EARTH ROTATION AND REVOLUTION: DEVELOPMENT OF GEOROTATION MEDIA FOR LEARNING DIGITAL GEOGRAPHYLearning media is an intermediary in the delivery of information through various channels. The information conveyed can provide stimulation to students both in terms of thoughts, to the will that can improve the learning process. The use of learning media in geography can help students describe, describe, or describe things that are abstract and difficult to understand. This development research aims to develop a learning media in the form of applications that can be accessed on smartphones. This development research method uses ADDIE (Analyze, Design, Development, Implementation, Evaluation). The types of data in this development research are qualitative data and quantitative data. Qualitative data were obtained from criticism and suggestions from expert validators and trial respondents. Quantitative data in this development research is in the form of numerical scores in the questionnaire obtained from expert validators and trial respondents. The Georotation in this study has been tested on 36 students of class X-D SMAN 2 Probolinggo. The results of research on the development of Georotation media obtained a percentage of 98 percent of media expert validators, 77 percent of material expert validators, 97 percent of teacher responses, 83 percent of student responses as test subjects. Thus the results show that the development of Georotation very suitable for use in learning geography.Media pembelajaran sebagai perantara untuk merangsang kemampuan berpikir peserta didik dalam proses pembelajaran. Penelitian pengembangan ini bertujuan untuk mengetahui kelayakan media pembelajaran Georotation yang dikembangkan untuk pembelajaran geografi. Desain penelitian pengembangan ini menggunakan ADD (Analyze, Design, Development), merupakan bentuk modifikasi desain penelitian ADDIE. Jenis data dalam penelitian pengembangan ini yaitu data kualitatif dan data kuantitatif. Data kualitatif diperoleh dari kritik dan saran oleh validator media, validator materi, dan responden uji coba. Data kuantitatif dalam penelitian pengembangan ini berupa skor angka dalam angket yang diperoleh dari validator materi, validator media, dan responden uji coba. Produk Georotation pada penelitian ini telah diuji cobakan kepada siswa kelas X-D SMAN 2 Probolinggo sejumlah 36 peserta didik. Hasil penelitian pengembangan Media Georotation memperoleh persentase 98 persen dari validator ahli media, 77 persen dari validator ahli materi, 97 persen dari tanggapan guru, 83 persen dari tanggapan peserta didik sebagai subjek uji coba. Dengan demikian hasil menunjukkan, bahwa pengembangan media pembelajaran Georotation sangat layak digunakan dalam pembelajaran geografi.